Transformational Leadership on Teachers' Performance Mediated by Teacher Satisfaction - Mardalena, Mardalena; Sarinah, Sarinah; Taufan, Ade; Melina, Angra; Hayati, Hayati; Yunus, Mukhlis; Elfisa, Yesi; Saukani, Saukani (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to determine the effect of transformational leadership on teacher performance mediated by teacher satisfaction on Tahfidzil Quran Lebay Yasin Boarding School. A quantitative approach and explanatory research will be used in this research. Primary data comes from questionnaires of variables, while secondary data comes from school data, textbooks, and journals. The population were 41. The sample was used through non-probability sampling purposive sampling, were 41. The data analysis techniques used SEM PLS by SmartPLS 3. The results of this study indicate that there was significant direct effect of transformational leadership on teacher performance t-statistic 2.444 > 1.96 p-value 0.015 or (p < 0.05), transformational leadership on teacher satisfaction t- statistic 10.319 > 1.96 p-value 0.00 or (p < 0.05), teacher satisfaction on teacher performance t-statistic t-statistic 21.404 > 1.96 p-value 0.00 or (p < 0.05), The result also discovered that there was significant indirect effect of transformational leadership on teacher performance mediated by teacher satisfaction t-statistic 8.232 > 1.96 p-value 0.00 or (p < 0.05). So, the school leader was recommended to empower and develop peer relationships in order to achieve teacher performance effectively.